지역냉방용 직접순환식 아이스슬러리 시스템의 현장적용 사례 - 유호선; 이상훈; 이윤표 (대한설비공학회, 2009)
In order to investigate the feasibility of a direct ice slurry transporting system for the purpose of district cooling, a case study of field application is performed. The research aims include the field measurement of ice packing factor, the performance of coldness delivery, and the branching characteristics of ice slurry. Two representative types of pipe branch are dealt with in this work. For the slurry flow with ice volume fraction of 0.16 or less, the pipe blocking due to aggregation is not observed. Based on the time-wise variation of temperature in the storage tank, a calculating method of ice packing factor is newly developed, which seems to be useful when the brine concentration is unknown. It is confirmed that the mass flow rate of ice slurry per unit cooling load is markedly reduced with increasing the ice content. The pumping power also decreases, but remains unchanged for high ice fractions. The distribution of ice particle before and after branching shows a good uniformity within the range of 5% difference, but yields a unique trend depending on the flow rate.